Understanding Fatigue in Sjögren’s Syndrome: Outcome Measures, Biomarkers and Possible Interventions - Mæland, Elisabeth; Miyamoto, Samira T.; Hammenfors, Daniel; Valim, Valeria; Jonsson, Malin V. (Frontiers in Immunology, 2021)
Sjögren’s syndrome (SS) is an autoimmune disease affecting the salivary and lacrimal glands. Symptoms range from dryness to severe extra-glandular disease involving manifestations in the skin, lungs, nervous system, and kidney. Fatigue occurs in 70% of patients, characterizing primary SS (pSS) and significantly impacting the patient’s quality of life. There are some generic and specific instruments used to measure fatigue in SS. The mechanisms involved with fatigue in SS are still poorly understood, but it appears fatigue signaling pathways are more associated with cell protection and defense than with pro-inflammatory pathways. There are no established pharmacological treatment options for fatigue in pSS. So far, exercise and neuromodulation techniques have shown positive effects on fatigue in pSS. This study briefly reviews fatigue in pSS, with special attention to outcome measures, biomarkers, and possible treatment options.